Avaliação da atividade cicatrizante do extrato etanólico e do Triterpeno 3, 6 , 16 Trihydroxylup-20 (29) - Eno provenientes de folhas de Combretum leprosum mart. no tratamento de lesões cutâneas induzidas em camundongos - Assis, Lívia Coelho de (2015)
Wound healing is a complex and dynamic process involving an integrated action of several cell types, extracellular matrix and soluble mediators such as cytokines, which serve to recover the integrity of damaged anatomical structure. Natural products are the basis for many biotechnological inputs, as they are biologically active compounds with great potential for therapeutics and can provide molecular basis for many drugs in the clinics. Combretum leprosum Mart. is a native species of Caatinga, important biome in the Brazilian semiarid region, being popularly used in Brazil for the treatment of many diseases such as skin diseases. This study aimed to investigate the pro-healing potential of the ethanol extract (EECL) and the bioactive triterpene 3β, 6 β, 16 β-trihydroxylup-20 (29) ene (CLF-1) isolated from leaves of C. leprosum. Cell migration assay was performed using fibroblasts, which were treated with CLF-1 (1.75 µg / ml and 2.5 µg / ml) and analyzed after 0, 6 and 24 hours. Skin wounds (1 cm2) were induced in the dorsal region of mice (n = 30) and were treated with daily topical application (100µl) according to the group: saline, EECL (100μg / ml) and CLF-1 (100μg / ml) for 12 days. The results showed that CLF-1 did not show toxicity to fibroblasts and further increased cell proliferation and migration so that a significant increase on injury closing percentage was observed using both concentrations (1.75 mg / ml vs 2.5 mg / mL,) compared to control (p <0.05). Within 24 hours, there was also a significant increase in the rate of migration comparing CLF-1 at 2.5 ug / ml and control group (p<0.05). For the in vivo analysis, on the 2nd post surgical day (PS), the lesions treated with EECL and CLF-1 showed moderate presence of vessels in granulation tissue progressing to the dermis, as well as a slight inflammatory infiltrate. It was also observed that, on the 7th PS day, the animals treated with CLF-1 showed moderate angiogenesis, whereas animals treated with saline showed cell proliferation and migration into the wound. Furthermore, on the 12th day PS, the animals treated with EECL and CLF-1 showed complete closing of the injury, while those receiving saline exhibited open wounds. Thus, it was concluded that EECL and CLF-1 showed pro-healing effects, as well as a possible anti-inflammatory action and additional research is needed to elucidate its mechanisms in the wound healing process.